Smoking cessation in the first trimester reduces most obstetric risks, but not the risks of major congenital anomalies and admission to neonatal care: a population-based cohort study of 1 164 953 singleton pregnancies in Finland. Issue 2 (24th October 2013) - Räisänen, Sari; Sankilampi, Ulla; Gissler, Mika; Kramer, Michael R; Hakulinen-Viitanen, Tuovi; Saari, Juho; Heinonen, Seppo
Abstract : Background: In industrialised countries, approximately 5–20% of women smoke during pregnancy. We aim to study the association between smoking during pregnancy and adverse perinatal outcomes. Methods: A retrospective population–based cohort study using data on all singleton births between 1991 and 2010 (n=1 164 953) derived from the Finnish Medical Birth Register. Results: Of all the mothers included, 82.3% were non-smokers, 2.6% quit smoking during the first trimester of pregnancy, 12.5% smoked throughout pregnancy and 2.7% had no information on smoking. Continuing smoking after the first trimester of the pregnancy was associated with an increased prevalence of admission to a neonatal intensive care unit, stillbirth, preterm birth (<37 gestational weeks), low birth weight (LBW, <2500 g), small for gestational age (SGA, <−2 SDs) and major congenital anomaly compared with non-smokers. Smoking cessation reduced the risk of prematurity, stillbirth, LBW and SGA close to or at similar levels as those of non-smokers. Tobacco exposure in early pregnancy resulted in a 19% increased prevalence of admission to neonatal intensive care unit and a 22% increased prevalence of major congenital anomaly compared with non-smokers. Conclusions: Smoking cessation appeared to reduce pregnancy risks close to those of non-smoking peers. Exposure to early pregnancy smoking was, however, associated with an increased admission to neonatal intensive care and an increased prevalence of major congenital anomalies.